Dinamika Tekanan Media Sosial, Dukungan Sosial, dan Kepercayaan Diri Atlet Sepak Bola - Shilva Putri Pramono; An Riwi Widyastuti; Brigitan Argasiam (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study is motivated by rising psychological pressure on athletes from social media and the importance of social support for self-confidence. It analyzes the effect of social media pressure and social support on the self-confidence of Persipa Pati football players. Using a quantitative explanatory design, data were collected from all 116 players through total sampling with a Likert-scale questionnaire measuring social media pressure, social support, and self-confidence, then analyzed using multiple linear regression. Results show that social media pressure negatively affects self-confidence, while social support has a positive effect; together, both variables significantly influence players’ self-confidence. These findings indicate that athletes’ self-confidence depends not only on internal factors but also on digital social dynamics and social support received. Managing social media pressure and strengthening social support are therefore essential for improving athletes’ psychological condition.